2022
DOI: 10.1002/maco.202213582
|View full text |Cite
|
Sign up to set email alerts
|

Field exposure study under sheltered and open exposure conditions at different test sites in Germany: First‐year corrosion rate and atmospheric corrosivity

Abstract: The corrosivity of atmospheres in Europe has changed significantly in recent decades. For the Federal Republic of Germany, no current values for the corrosion rate based on 1-year atmospheric exposure of standard specimens can be found in the scientific literature after 2000. This paper presents results from a field exposure study in the Berlin metropolitan area and Helgoland in 2016. Based on standard specimens, values for the corrosion rate and the corresponding atmospheric corrosivity category are determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…However, in the case of copper, Al, and weathering steel, the trend is reversed when they are exposed to industrial or marine environments. 8,21 Studies discussing these exposure conditions in the atmospheric corrosion of Mg-Al alloys are scarce. [18][19][20] Liao and Hotta 18 compared the mass loss of AZ31B specimens under unsheltered and sheltered environments and found that the unsheltered specimens exhibited much higher mass loss.…”
mentioning
confidence: 99%
“…However, in the case of copper, Al, and weathering steel, the trend is reversed when they are exposed to industrial or marine environments. 8,21 Studies discussing these exposure conditions in the atmospheric corrosion of Mg-Al alloys are scarce. [18][19][20] Liao and Hotta 18 compared the mass loss of AZ31B specimens under unsheltered and sheltered environments and found that the unsheltered specimens exhibited much higher mass loss.…”
mentioning
confidence: 99%